Recent trends in algebraic development techniques : 23rd IFIP WG 1.3 International Workshop, WADT 2016, Gregynog, UK, September 21-24, 2016, Revised selected papers /: 23rd IFIP WG 1.3 International Workshop, WADT 2016, Gregynog, UK, September 21-24, 2016, Revised selected papers. (2017) - Unknown
No abstract available